Long term change in chemical properties of preindustrial charcoal particles aged in forest and agricultural temperate soil. (May 2017) - Hardy, Brieuc; Leifeld, Jens; Knicker, Heike; Dufey, Joseph E.; Deforce, Koen; Cornélis, Jean-Thomas
Highlights: Cultivation increased sharply association of charcoal with soil minerals. Ageing and cultivation decreased resistance of charcoal to chemical oxidation. Oxygenation through ageing decreased thermal resistance of charcoal. Preindustrial charcoal contained three fractions of distinct thermal resistance. Abstract: Black carbon (BC) plays an important role in terrestrial carbon storage. Nevertheless, the effect of cultivation on long term dynamics of BC in soil has been poorly addressed. To fill this gap, we studied the chemical properties of charcoal particles extracted from preindustrial kilns in Wallonia, Belgium, along a chronosequence of land use change from forest to agricultural soil, up to 200 years of cultivation. Preindustrial charcoal samples were compared with charcoal subjected to short term ageing in a currently active kiln. Cultivation increased the association of charcoal with soil minerals, which is favored by deprotonation of carboxylic acids under liming, thereby enhancing the reactivity of charcoal toward mineral surfaces. The large specific surface area of charcoal, related to its porosity, promotes the precipitation of 2:1 phyllosilicates and CaCO3 . Both ageing and cultivation decreased the resistance of charcoal to dichromate oxidation, related to an increase in the H/C of charcoal. Differential scanning calorimetry revealed the presence of three fractions of distinct thermal stability. Saturation of carboxylate groups with Ca 2+ under liming decreased the thermal stability of the O-rich, less thermally stable fraction of charcoal. This fraction decreased over time of cultivation, leading to a relative accumulation of the thermally most stable fraction of charcoal. This might result from the preferential loss of the O-rich fraction or the slowdown of charcoal from oxidation via association with minerals. Our results highlight the idea that land use significantly affects the properties of BC through the modification of soil conditions, which might influence the kinetics of BC loss from soil.